Modeling study and experimental investigation of SPSR and solid particles–sCO2 heat exchanger for concentrating solar power plant. (November 2022) - Hu, Feng; Wang, Zhifeng; Bai, Fengwu; Yu, Yupu
Abstract: Solid particle solar receiver (SPSR) and solid particles-supercritical carbon dioxide (sCO 2 ) heat exchanger (HX) are critical units for energy concentration and conversion in innovative concentrating solar power (CSP) plant, and their property will have great impact on the sCO 2 -CSP integrated system. The SPSR is receiving increasing attention owing to the higher operation temperature potentially to lower the cost of the integrated. The significance of solid particles–sCO 2 HX cannot be underestimated, since the energy conversation assimilated from solid particles of the SPSR can be transferred to sCO 2 rapidly and efficiently to directly impact the whole efficiency of the integrated system. In this paper, mathematical models of quartz tube bundles SPSR and fluidized bed solid particles–sCO 2 HX were established. Furthermore, based on the first solar power tower plant in Asia, on-sun experiments were carried out, the total operation time exceeded 103 h. The experimental results show that when 59 heliostats are used, the direct normal irradiance is 865 W/m 2, and the remaining time is 351 s, the maximum output temperature can reach 871.6 °C. In addition, by comparing the simulation results with the experimental values, it indicates the established models possess high degree of accuracy. The study extends to the dynamic simulation and control strategy, and puts forward suggestions for the system optimization and operation regulation of the sustainable power system on electrical engineering and green energy.